Leadership and management skills - Fontaine, Rodrigue Ancelot Harvey (IIUM Press, 2016)
This book is the summary of his 15 years of experience. Leadership and management skills can be learned. However, it doesn't happen by accident. This book offers a simple process to do so. First, one must be involved in a semester long project that pushes you outside your comfort zone. Second, it requires keeping a journal and reflecting on the journey. Once readers become familiar with this process, developing leadership and management skills is a question of time and effort.